Assessment of nutritional knowledge and practice on healthy eating at hawker stalls centre among adults in the city of Kuala Terengganu - Ismail, Nur Syahira (Universiti Sains Malaysia, 2016)
Eating out, especially at a hawker stalls has been often regarded as a Malaysian culture. However, it is not clear whether people are aware of nutrition and healthy eating practice when eating out at hawker stalls. As such, this study was conducted to determine the nutritional knowledge and practice on healthy eating when eating out at hawker stalls among adults in Kuala Terengganu. This is a quantitative and cross-sectional study, a questionnaire (socio-demographics, frequency of eating out, nutritional knowledge, and practice on healthy eating) was used to collect the data at two main hawker’s centre in Kuala Terengganu (Taman Shah Bandar and China Town). A total of 137 respondents, where more female (n=88, 64.2%) than male (n=49, 35.8%) participated in this study. Majority were Malays (n=124,90.5%) followed by Chinese (n=l 1, 8.0%) and India (n=2, 1.5%). Regardless of the knowledge of respondents, most of them have a good knowledge on classification foods into group (n=128, 93.4%) and poor nutritional knowledge (n=7, 5.1%). Their practice of eating habits mostly unhealthy practices (n=123, 89.8%) and healthy (n=12, 8.8%). However, findings were significant association between the nutritional knowledge and practices of healthy eating (p=0.000, p<0.05). Therefore, it can be conclude that nutritional knowledge is necessary for changes in consumer’s food behaviours.